All‐Fiber Optical Waveform Converter Based on Deformed Catenary Nanostructure. Issue 11 (4th November 2021) - Zhang, Wentao; Luo, Zhongyue; Wang, Rui; Jiang, Xiaowen; Liu, Houquan; Deng, Shijie; Chen, Ming; Yuan, Libo; Deng, Hongchang
Abstract : Optical Waveform Converter In article number 2100042, Hongchang Deng, Houquan Liu, and co‐workers have designed an all‐fiber waveform converter by integrating one‐dimensional long helical fiber grating and two‐dimensional deformed catenary nanostructure. Through wavelength and circular polarization modulation, the device has a unique ability in optical focusing, divergence and rotation, which can make the generated light beam break through the diffraction limit. It has potential applications in optical manipulation and imaging.